Desvelando cercas: o cenário da educação básica do e no campo no estado do Tocantins - Santos, Thiago Ferreira dos (Universidade Federal do Tocantins, 2017)
The objective of this study was to map the reality of the Basic Education of the and in the Field in the state of Tocantins – from a bibliographical and documentary research and considering the settlement schools, quilombos communities remnant, indigenous territories, rural communities and agricultural family – with regard to the number of school units and enrollment, teaching conditions and public policies aimed at this education category. In order to achieve this, the following specific objectives were pursued: conduct a survey the state's basic education schools in the field, as well as verifying the quantitative of these school units and their enrollments; as well as to describe the conditions of basic education teaching in these schools, identifying the public policies aimed at the educational service of peasants. This is a descriptive-analytical, predominantly qualitative approach, and as strategies and procedures for data collection the present study was organized in stages: i) a review of bibliographies related to the object and subject of study, such as: the Brazilian peasantry and its formation, the conflicts of the struggle for land and social movements; Rural Education and Field Education; Field Education – references, traits and principles; Field Education in Brazilian legislation; The Basic Education of the Field; Public policies for the field and for the Education of the Field and, finally, a little of the locus of the research, the State of Tocantins; ii) collection of documents (resolutions, ordinances, censuses, among others) related to the Basic Education of the Field in Tocantins in the years of 2013 to 2016; iii) description and systematization of collected data; and, iv) analysis and discussion of information. The data collected and analyzed indicate that, the Field Education in Tocantins, is still in the process of construction. There are a large number of schools that – even though they are in the rural areas – cannot be considered as "field schools”, but "in the field". For the most part, they are institutions that are not thought out and created by social movements and people living in and out of the country, follow an urban curriculum and do not comply with the guidelines for the Field Schools. In addition, issues such as infrastructure (classrooms, libraries and laboratories, leisure areas, etc.), logistics (school transport), teacher training of the professionals that work in these spaces, and design and teaching proposal (Alternation Pedagogy) are far from the minimum quality required for its operation.